Analisis Strategi Penerapan Kurikulum Merdeka di Madrasah Aliyah Negeri 2 Probolinggo - Ismatul Izzah; Mohamad Ahyar Ma’arif; Nur Fatimah (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
This study aims to analyze the strategies for implementing the Independent Curriculum (Kurikulum Merdeka) at Madrasah Aliyah Negeri (MAN) 2 Probolinggo. The research focuses on curriculum planning, implementation, and evaluation, with particular attention to the principal’s role in resource management, teacher capacity building, support for project-based learning, and the utilization of the P5 Report Application as an evaluation tool. The research employs a descriptive qualitative approach, gathering data through interviews, observations, and document analysis. The findings reveal that the principal plays a strategic role in ensuring the effective implementation of the Independent Curriculum by optimizing resource potential, strengthening teacher competence through continuous training, and supporting innovative learning methods aligned with students' needs. Curriculum evaluation is conducted periodically through evaluation meetings and the use of technology, providing data-driven insights for strategic decision-making. This study offers significant recommendations for developing the Independent Curriculum in madrasahs, particularly in fostering inclusive, meaningful, and student-centered learning.